2013
DOI: 10.1073/pnas.1314395110
|View full text |Cite
|
Sign up to set email alerts
|

Conformational inactivation induces immunogenicity of the receptor-binding pocket of a bacterial adhesin

Abstract: Significance Antibodies targeting the receptor-binding pocket of viral and bacterial adhesins are highly protective against infection. However, functional site epitopes in the antigens are not always highly immunogenic, possibly because of the binding epitope-masking effects of natural ligand–receptor interactions. By using the mannose-specific fimbrial adhesin of Escherichia coli , FimH, we demonstrate that locking the adhesin in a low-binding conformation abroga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 32 publications
(38 reference statements)
1
23
1
Order By: Relevance
“…6 and 7) revealed an altered protein conformation in the ligand-free state that was converted to a conformation similar to WT FimH LD upon mannoside addition. In contrast to previously suggested lock in the low-affinity conformation of these mutants (5,38,40), this demonstrates for the first time a considerable conformational change of the isolated FimH LD in the absence of the regulatory pilin domain. For the mutant V67K, designed to destabilize the helical ␣-switch region of the highaffinity FimH LD , binding affinity and kinetics were only mildly affected, suggesting solely a weak coupling between the ␣-switch region and the binding pocket.…”
Section: Allosteric Regulation Of the Bacterial Adhesin Fimhcontrasting
confidence: 95%
See 3 more Smart Citations
“…6 and 7) revealed an altered protein conformation in the ligand-free state that was converted to a conformation similar to WT FimH LD upon mannoside addition. In contrast to previously suggested lock in the low-affinity conformation of these mutants (5,38,40), this demonstrates for the first time a considerable conformational change of the isolated FimH LD in the absence of the regulatory pilin domain. For the mutant V67K, designed to destabilize the helical ␣-switch region of the highaffinity FimH LD , binding affinity and kinetics were only mildly affected, suggesting solely a weak coupling between the ␣-switch region and the binding pocket.…”
Section: Allosteric Regulation Of the Bacterial Adhesin Fimhcontrasting
confidence: 95%
“…Interestingly, such a conformation accurately resembles the medium-affinity state observed in the crystal structure of the mannoside-bound FimH FL (23). Indirectly, this is evidenced by the observation that an inhibitory antibody raised against the FimH LD mutant V27C/L34C, with an epitope in the binding pocket, strongly binds to FimH in the high-affinity state (40), which displays a nearly identical geometry of the binding pocket compared with the medium-affinity state (23). However, the exact conformation of V27C/L34C and R60P in the bound state remains to be confirmed, e.g.…”
Section: Allosteric Regulation Of the Bacterial Adhesin Fimhmentioning
confidence: 62%
See 2 more Smart Citations
“…Notably, the actual proteins used in these studies consisted of either a natural adhesion-competent truncate of FimH or a bimolecular complex of the adhesin and its cognate chaperone for both FimH and PapG, unlike our use here of a donor strand complemented derivative of CfaE. Interestingly, recent studies of FimH have demonstrated the existence of low-and high-affinity binding conformations and suggest that locking FimH into its low-affinity state results in enhancement of adhesion-neutralizing antibodies (30,31). To date, structural evidence indicates that dscCfaE exists in a low-affinity conformational state, while a high-affinity state has been postulated but not proven (16,17,32).…”
Section: Discussionmentioning
confidence: 99%